Context and Implications Document for: A systematic review of the literature on the causes of early school leaving in Africa and Asia. Issue 3 (25th September 2018) - Momo, Michelle S. M.; Cabus, Sofie J.; De Witte, Kristof; Groot, Wim
Abstract : This guide accompanies the following article: Momo, M. S. M., Cabus, S. J., De Witte, K. & Groot, W. (2018) A systematic review of the literature on the causes of early school leaving in Africa and Asia. Review of Education, https://doi.org/10.1002/rev3.3134